Understanding Group Dynamics and Typology of Youth Travelers: A Comprehensive Study on Travel Preferences and Roles at Destination - Kusumah, Ahmad Hudaiby Galih (Journal of Indonesian Tourism, Hospitality and Recreation, 2023)
ABSTRACTThis research explores the group dynamics and typology of young travelers, classifying them into four distinct types: Leaders, Followers, Clowns, and Loners. Leaders assume responsibility for group decision-making and itinerary management, often prioritizing group comfort over personal enjoyment. Followers comply with group decisions and adapt their preferences to align with collective choices. Clowns, serving as group entertainers, contribute to a positive atmosphere, while Loners prefer solitude, engaging in personal activities even within the group context.  The research highlights the concept of a "collective bubble," a combination of physical and psychological factors that contribute to an enjoyable group travel experience. Several factors contributing to unpleasant group travel experiences were also identified, including inadequate planning time, excessive anxiety, personal issues between group members, significant differences in personal preferences, unexpected events like illness, and comparisons with other groups' experiences. The findings underscore the importance of understanding the typologies and dynamics of youth travelers in creating satisfying group travel experiences. The roles played by different traveler types and effective compromise among group members emerge as key factors for enjoyable group travel. The study provides valuable insights for organizers and participants of group travel, contributing to the literature on youth tourism and group dynamics. ABSTRAKPenelitian ini mengeksplorasi dinamika kelompok dan tipologi pelancong muda, mengklasifikasikan mereka menjadi empat tipe berbeda: Pemimpin, Pengikut, Badut, dan Penyendiri. Pemimpin memikul tanggung jawab untuk pengambilan keputusan kelompok dan manajemen rencana perjalanan, seringkali memprioritaskan kenyamanan kelompok daripada kesenangan pribadi. Pengikut mematuhi keputusan kelompok dan menyesuaikan preferensi mereka agar selaras dengan pilihan kolektif. Badut, berfungsi sebagai penghibur kelompok, berkontribusi pada suasana positif, sementara penyendiri lebih suka menyendiri, terlibat dalam aktivitas pribadi bahkan dalam konteks kelompok. Penelitian tersebut menyoroti konsep "gelembung kolektif", kombinasi faktor fisik dan psikologis yang berkontribusi pada pengalaman perjalanan kelompok yang menyenangkan. Beberapa faktor yang berkontribusi terhadap pengalaman perjalanan kelompok yang tidak menyenangkan juga diidentifikasi, termasuk waktu perencanaan yang tidak memadai, kecemasan yang berlebihan, masalah pribadi antara anggota kelompok, perbedaan preferensi pribadi yang signifikan, kejadian tak terduga seperti sakit, dan perbandingan dengan pengalaman kelompok lain. Temuan ini menggarisbawahi pentingnya memahami tipologi dan dinamika wisatawan muda dalam menciptakan pengalaman perjalanan kelompok yang memuaskan. Peran yang dimainkan oleh tipe pelancong yang berbeda dan kompromi yang efektif di antara anggota grup muncul sebagai faktor kunci untuk perjalanan grup yang menyenangkan. Studi ini memberikan wawasan berharga bagi penyelenggara dan peserta perjalanan kelompok, berkontribusi pada literatur tentang pariwisata kaum muda dan dinamika kelompok.